SURVIVAL AMIDST COVID-19 PANDEMIC: CONTRIBUTIONS OF THE FOREST TO THE LIVES OF THE FILIPINOS - John Louie M Bona; Kim Vincent M Timbal; Jaypee D Bangate; Michelle A Resueño; Ericson Esquibel Coracero; RB Juarez Gallego (Indonesian Journal of Forestry Research, 2023)
COVID 19 has brought significant damage to the lives of the people due to extremely long lockdowns and unemployment. Thus, leaving no choice to the residents and forcing them to rely on what is available in the environment. This study was conducted to assess the contribution of the forests to the lives of the locals in Aurora through a survey on 161 respondents. Data were analyzed through descriptive statistics including frequency, mean, rank, and percentage. Results showed that 100% of the respondents depend on the forests for their food which includes fruits and vegetables in the wild and on their farms located in and along the forest. Meanwhile, 116 individuals (72%) obtained livelihood from the forest in times of the pandemic in the form of labor, farming, selling of forest goods, charcoal making, and furniture making. Generally, the individual income obtained from forest ranged from Php500.00 (8.85 USD)to Php25,000.00 (442.65 USD) and an overall mean individual monthly income of Php4,084.19 (72.32 USD).  Each type of livelihood activity provided a mean monthly income ranging from Php 4350 (USD 77.02) to Php 9021 (159.73 USD) per person. However, the respondents faced challenges such as loss of products due to theft, the limited number of consumers, and struggles concerning the health of the workers especially the elders, disabled, and other high-risk individuals to COVID-19. The government must consider providing needs (financial, technical, knowledge) to the locals in obtaining products and services from the forest for sustainable utilization of the resources. This research dictate the importance of forest as a source of life to the people. Thus, the result of this study may be used as a baseline for the government in crafting policies to help ensure sustainability of the forest and the lives of the society.